Investigating Students’ Levels and Challenges in Promoting Autonomous Learning:: A University EFL Context in Indonesia - Wardani, Dwi Anjar Fitriyah Kusuma; Nur Yusuf , Fazri (International Journal of Language Teaching and Education, 2026)
Over the past three decades, autonomous learning has emerged as a hot topic in language learning. This study investigates the learner autonomy levels and the challenges faced by English as a Foreign Language (EFL) learners in an Indonesian university context. Using a qualitative method, data were collected through a structured survey with 30 participants and follow-up interviews with four graduate students. The survey is based on Bandaranaike & Willison’s framework. The results were analyzed using thematic analysis by Braun & Clarke (2006). Results revealed that learners showed moderate autonomy, confidence in guided tasks, critical thinking, but faced challenges in initiating independent tasks, managing time, planning objectives, managing communication, and relying on teacher guidance. Future research could investigate more on the ICT application in enhancing students’ autonomous learning.